2018
DOI: 10.5489/cuaj.5084
|View full text |Cite
|
Sign up to set email alerts
|

Malignant websites? Analyzing the quality of prostate cancer education web resources

Abstract: The reliability of websites presenting prostate cancer information is questionable. There were noted deficiencies in attribution, currency, and readability. While information on detection and treatment is well-covered, information related to prognosis is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…At the same time, there is a need to improve the quality of prostate cancer websites. When systematically reviewed by Black and Penson in 2006 [38] and again by Kobes et al in 2018 [39], websites containing information on prostate cancer were found to be lacking in currency, attribution, balance of evidence, and comprehensiveness. In another study, only 3 of 62 websites containing information on prostate cancer treatment options were written below the recommended high school reading level [40].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there is a need to improve the quality of prostate cancer websites. When systematically reviewed by Black and Penson in 2006 [38] and again by Kobes et al in 2018 [39], websites containing information on prostate cancer were found to be lacking in currency, attribution, balance of evidence, and comprehensiveness. In another study, only 3 of 62 websites containing information on prostate cancer treatment options were written below the recommended high school reading level [40].…”
Section: Discussionmentioning
confidence: 99%
“…An internet search was conducted using the term "cervical cancer" in Google and two metasearch engines (Yippy and Dogpile) on April 25, 2018. These engines were chosen for consistency with previous studies from our research group [15][16][17]. Briefly, Google is used due to its popularity in English speaking countries, while Yippy and Dogpile compile results across an aggregate of engines (including Google, Bing and Yahoo).…”
Section: Methodsmentioning
confidence: 99%
“…The tool was developed in 2009 through a detailed review of available resources for evaluating the quality of medical information on the internet and adaptation of several existing guidelines and validated tools [18]. It has been previously validated for inter-rater reliability and usability by our research group, and has been used to evaluate online information quality for other cancers [15][16][17]. Accountability criteria are derived from the Health on the Internet (HON) code principles and the DISCERN scale, an instrument designed to assist those without content expertise in evaluating written health information [19,20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, systematic reviews assessing the quality of health information online have consistently shown that health websites tend to be lacking in currency, attribution, balance of evidence, readability, and comprehensiveness. [25][26][27][28] Although efforts to improve the quality of health information online are certainly needed, the participatory nature of the web means that the internet will continue to include unvetted health information. Therefore, of equal importance are efforts to boost the eHealth literacy of cancer survivors and their ability to triangulate information from multiple sources and participate in improving health information online.…”
mentioning
confidence: 99%